Negotiating Dissonance between the Religious, the Civil and the Legal in Anglican Same-Sex Weddings - Bethmont, Rémy (Studies in church history, 2023)
With the adoption of same-sex marriage or marriage-like schemes by civil authorities on both sides of the North Atlantic, Anglican same-sex couples in England, Scotland and the United States have had to negotiate various forms of dissonance between the religious celebration and the legal or civil status of their unions. This often translates into couples having multiple celebrations of their unions in order to bring together the legal and the religious creatively. These multiple ceremonies evidence the grip exercised by the tradition of a single wedding ritual that is both religious and legal on the imagination of Anglican same-sex couples. Enduring attachment to this tradition has given rise to particular LGBTQ ways of relating the celebration of a union to time, thus contributing to the unravelling of a rigidly legal Anglican understanding of the marriage rite.